A meta-synthesis of care and support for older adults in Africa. Issue 1 (2nd January 2023) - Awuviry-Newton, Kofi; Tavener, Meredith; Wales, Kylie; Denham, Alexandra M.J.; Byles, Julie
ABSTRACT: This meta-synthesis joins together qualitative evidence on the care and support provision for older adults in an African context employing the World Health Organisation International Classification of Functioning, Disability and Health (WHO-ICF) framework, and Ethics of Care theory as organizing schema. A search of electronic databases, plus other relevant sources produced 465 articles from which nine met inclusion criteria. The synthesis identified findings improving our understanding of the care needs of older adults, and caregiving commitment thoroughly classified by the WHO-ICF and the ethics of care theoretical frameworks. This meta-synthesis reveals the strengths and gaps in knowledge from existing studies and draws attention to the need for further research targeting older adults and caregivers' needs in Africa.